Peningkatan Pelayanan Sosial Bidang Rehabilitasi Sosial Dinas Sosial Provinsi Sumatera Utara Secara Adaptif, Responsif, Terstruktur dan Sistematis - Payandro Doni Saputra Sitanggang; Berlianti Berlianti; Fajar Utama Ritonga (Yayasan Literasi Sains Indonesia, 2023)
Social services are the duties and responsibilities of a country for existing social welfare problems. Social Welfare Requirements (PPKS) who are individuals, families, groups and/or communities who, due to an obstacle, difficulty or disturbance, are unable to carry out their social functions, so they need social services to meet their needs both physically and spiritually as well as socially adequately and It is natural to have different root causes and problem solving according to the type. The process of re-functionalization and development to enable a person to be able to carry out his social function properly in the life of the community then requires accelerated steps to achieve social rehabilitation itself. Program methods that are adaptive, responsive, structured and systematic will always respond to developments and adjustments to social welfare issues themselves. The Provincial Social Service as the task-bearer to assist the Governor in carrying out government affairs in the social sector and assistance tasks assigned to the Regions are always expected to be able to present an influential and quality accelerated acceleration of social services.